Integrating Strategic Planning For School Administrators' Effectiveness in Public Senior Secondary Schools in Ilorin East Local Government Area, Kwara State - Afeez Adeshina SHITTU; Monsurat Iyabo ALAO; Ganiyat MAHMOUD-KASANDUBU; Idris ADAM; Latifat ABDULLATEEF (EDUCATION JOURNAL OF INDONESIA, 2026)
Education plays a significant role in national development, and the effectiveness of school administration is essential for achieving educational goals. However, many public secondary schools in Nigeria continue to experience administrative challenges such as poor planning, ineffective supervision, inadequate communication, and inefficient resource management. This study therefore investigated the integration of strategic planning for school administrators’ effectiveness in public senior secondary schools in Ilorin East Local Government Area, Kwara State. The study adopted a descriptive survey research design. The population of the study comprised 854 teachers in 34 public senior secondary schools in Ilorin East Local Government Area, Kwara State. Using Krejcie and Morgan’s sample size determination method, a sample size of 266 teachers was selected from 19 public senior secondary schools. Data were collected using a researcher-designed instrument titled “Integrating Strategic Planning for School Administrators’ Effectiveness Questionnaire (ISPSAEQ).” The instrument yielded a reliability coefficient of 0.72. Descriptive statistics of mean and standard deviation were used to analyze the data collected from 258 returned copies of the questionnaire. The findings revealed that the level of strategic planning integration among school administrators was high. The study further showed that strategic planning positively influences administrators’ effectiveness through improved decision-making, instructional supervision, accountability, communication, and resource management. The findings also identified inadequate funding, lack of training, insufficient government support, and weak monitoring systems as major challenges affecting strategic planning integration. The study concluded that strategic planning significantly enhances effective school management and administrators’ performance in public senior secondary schools.